PENERAPAN PROJECT BASED LEARNING (PjBL) UNTUK MENIGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII4 SMP BABUSSALAM PEKANBARU - Lestari Ning Tyas Ning Tyas; Jalinu '; Elfis Suanto Suanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research is a class action research that aims to improve the learning process and to increase the student’s mathematics learning outcomes by applying Project Based Learning (PjBL). The subjects of this research are the student of class VII4 SMP Babussalam Pekanbaru at second semester of academic years 2014/2015, which amounts to 19 students. This research consists of two cycles, each cycle consists of four stages: planning, implementation, observation, and reflection. Data collected through observation and learning outcomes test.  Data analysis is done by observation data analysis and student’s mathematics learning outcomes data analysis. The action is successful if the scores of teacher’s activities and student’s activities increase in every meeting and the number of students who reach Minimum Mastery Criteria increases in every cycle. Scores of teacher’s activities from the first to the sixth meeting are 93.55, 94.45, 100, 100, 100, and 100. While the scores of student’s activities from the first to the sixth meeting are 93.33, 95.24, 100, 100, 100, and 100. Percentage students that reach knowledge Minimum Mastery Criteria in base score is 42.11% increase to 57.89% at the first cycle and 68.42% at the second cycle. The result of this research showed that Project Based Learning improve the learning process and increase the mathematics learning outcomes the students of class VII4 SMP Babussalam Pekanbaru at second semester of academic years 2014/2015. Key words: Mathematic learning outcomes, Project Based Learning, Class action research